Unsettling the West: Nation and Genre in Guy Vanderhaeghe’s The Englishman’s Boy - Calder, Alison (Studies in Canadian Literature, 2000)
Guy Vanderhaegh’s The Englishman’s Boy undermines the myths of Canadian innocence, and of the American frontier as an allegory of Romance and robust strength; it is ultimately self-referential, even self-critical, as the book-ended, stylistically distinct Assiniboine narratives point to the racist and one-sided perspective inherent to the Western genre itself. The rather hypocritical Canadian stance, that of embracing and rejecting America — dependent here, it is suggested, largely on financial matters — is paralleled by Hollywood’s negatively revisionist sense of history, of its avowal and denial of its own aggressive violence. Harry Vincent’s manipulation of his Canadian identity echoes the self-serving manipulation of Canadian and American history, both of which lay the blame for historical violence upon a dangerous "other."